A realist review of infant feeding counselling to increase exclusive breastfeeding by HIV-positive women in sub Saharan-Africa: what works for whom and in what contexts - Simangaliso Nyoni; Linda Sweet; Jacinta Clark; Paul Ward (BMC, 2019)
Abstract Background The most recent World Health Organization (WHO) guidelines on Human Immunodeficiency Virus (HIV) and infant feeding promotes exclusive breastfeeding (EBF) in resource limited settings for the prevention of mother to child transmission (PMTCT) of HIV. Literature reveals poor uptake of WHO feeding guidelines, with mixed feeding being a regular practice. In light of the limited success in EBF promotion, a realist review was conducted, analysing the use of feeding counselling to increase exclusive breastfeeding by HIV-positive women in sub Saharan-Africa, where the majority of HIV childhood infections occur. We considered what mechanisms were at play, for whom and in what circumstances they led to exclusive breastfeeding. Methods Because infant feeding counselling is a complex social intervention with a non-linear causal pathway for preventing mother to child HIV transmission, a realist methodology was chosen for this study. Using Pawson's five stage sequence for conducting realist reviews, the results are presented as a set of identified and refined context-mechanism-outcome (CMO) configurations. These CMO configurations were used to show how particular outcomes occurred in specific contexts due to a generative mechanism and were developed through identifying a review question and program theory, searching for primary studies, quality appraisal, data extraction and data synthesis. Results From an initial 1010 papers, 27 papers met the inclusion criteria and were used to refine the program theory. Exclusive breastfeeding occurred when a woman was motivated regarding motherhood, had correct learning and understanding about infant feeding practices through counselling, no fear of breastfeeding or the impact of opposing feeding related cultural beliefs, and the support from others to be assertive about their feeding choices when faced with pressure to mix-feed. An additional CMO configuration was added during the refinement of the program theory identifying that mothers needed to not just understand but also prioritize EBF advice over cultural beliefs and stigma. Conclusion The intended audience for this review are researchers and health care workers in PMTCT, particularly sub-Saharan Africa, who may benefit from the work that has been done to identify contexts for the success and failures of EBF.